The Jihadism in the Penitentiary System: The Case of Rida B - Barragán Márquez, Luis; Berdún Carrión, Salvador (Journal of the Spanish Institute for Strategic Studies, 2026)
The recent conviction of inmate Rida B. for threats against prison officials and glorification of terrorism has brought the issue of jihadist radicalization in prisons back into the spotlight. This phenomenon, however, has particular characteristics that differentiate it from jihadist radicalization and its criminal manifestations outside of prisons. The fact that convictions for jihadist activities in prisons have been handed down to inmates classified as first-degree raises key questions: How does jihadist activity manifest in a maximum-security environment? To what extent does the penitentiary institution succeed in preventing these phenomena?
Keywords: Terrorism; Prisons; Radicalization; Enhancement